An Ecological Study of Negro Juvenile Delinquency in Jacksonville, Florida, 1940-1947 - Shropshier, Lucile J. B. (1948)
Problem of the Study: - This problem will be concerned with a study of Juvenile Delinquency among Negroes in Jacksonville, Florida for the years 1940-1947. Background: - In this study we employed the survey method. The author's main technique was the personal interview with Juvenile Court officers, school principals, teachers, Parental Home Records, and records of public and private agencies and Juvenile Court records. The other techniques used were to gather and analyze data on housing economic status, health, recreation, churches, social agencies and other organizations or prophalaties that may help in the problem. Delinquency as a responsibility of the state of Florida dates back to 1822, the year in which Florida was organized as a state by Congress. It has not been possible to obtain statistical material which would give a complete picture of the amount of crime and delinquency divided by race, sex and offense, in Jacksonville, Florida and Duval County. The best available measure of the extent to which Negroes commit the most serious offenses in the number of persons committed to the state prison as reported in the Biennial Report of the Prison Division of the Department of Agriculture